FINANCIAL FRAUDS IN CORPORATE ENVIRONMENT THAT AROSE FROM THE FAILURE IN CORPORATE GOVERNANCE - Khari, Paaras Kumar (2020)
The study aims to identify corporate governance as a fundamental pillar of organisations. Whether it has been proving sufficient remains debatable as evidenced in my research. There have been failures in corporate governance as the study unfolds. Emphasis has been placed on the identification and detection measures which are considered necessary to strengthen the corporate governance code. Secondary research is conducted for the literature review based on the qualitative research method. The comprehensive literature review is based on the semi-structured interviews with the participants (P=7) which includes fraud experts, educationalists and executives from corporations. Inductive research is followed by condensing diverse raw information into basic formats to present an accurate and functioning situation of corporate governance mechanism. Participant’s inputs are analysed for practical understanding of the actual workings of corporate governance in different settings. The findings confirm that corporate governance can and does play a significant part in fraud prevention and smooth functioning of corporate mechanisms. Historically the practice of corporate governance has centred primarily on the activities of the board. However, the concept includes fraud risk assessments, prevention and detection of financial irregularities as well as expectation of high ethical moral code.